2021
DOI: 10.12688/gatesopenres.13288.1
|View full text |Cite
|
Sign up to set email alerts
|

Higher COVID-19 mortality in low-income communities in the City of Cape Town – a descriptive ecological study

Abstract: Background Cape Town, a South African city with high levels of economic inequality, has gone through two COVID-19 waves. There is evidence globally that low-income communities experience higher levels of morbidity and mortality during the pandemic. Methods Age-standardized COVID-19 mortality in the eight sub-districts of Cape Town was compared by economic indicators taken from the most recent Census (unemployment rate, monthly income). Results The overall Standardized Death Rate (SDR) for COVID-19 in Cape To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…Importantly, among those aged ≥40 years, mortality was associated with recent first HIV evidence, which, in this age group, could indicate delayed HIV diagnosis or start of ART, and thus suggests delayed HIV care access. The wave pattern observed in our study population (a relatively large first wave) mirrored that in the lower socio-economic status subdistricts in the WC [19,20], consistent with the burden of HIV in South Africa being disproportionately higher among the poor.…”
Section: Discussionsupporting
confidence: 79%
“…Importantly, among those aged ≥40 years, mortality was associated with recent first HIV evidence, which, in this age group, could indicate delayed HIV diagnosis or start of ART, and thus suggests delayed HIV care access. The wave pattern observed in our study population (a relatively large first wave) mirrored that in the lower socio-economic status subdistricts in the WC [19,20], consistent with the burden of HIV in South Africa being disproportionately higher among the poor.…”
Section: Discussionsupporting
confidence: 79%
“…Only one study from the WHO Africa region was found. This South African study by Hussey and colleagues 124 identified a socioeconomic gradient in COVID-19 mortality at the subdistrict level in Cape Town up to Feb 24, 2021.…”
Section: Covid-19 Mortality and Deprivationmentioning
confidence: 99%
“…These waves have resulted in high seroprevalence of ~70% from prior infection, especially in poorer communities where social distancing is challenging [ 11 , 12 ]. Whilst such high seroprevalence came at the cost of exceptionally high mortality during the first wave of COVID‐19, these areas were relatively protected from both infections and severe disease in subsequent waves [ 13 ]. For example, in the large urban township of Khayelitsha, the poorest subdistrict in Cape Town, anti‐nucleocapsid antibody seroprevalence resulting from prior infection was 45% by the end of wave one [ 11 ], increasing to >70% by the end of wave three (Nei‐Yuan Hsiao, personal communication).…”
Section: Introductionmentioning
confidence: 99%